Al-Alwani, Taha Jabir. “Naskh (Abrogration) is not a Distortion of the Qur'an,” Year 12, Issues 46-47 (Fall 1428 AH/ 2007 CE), Pp. 23-64. - العلواني, طه جابر (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2007)
Taha Jabir al-Alwani’s article addresses the issue of naskh (abrogation) in relation to the Qur'an; an issue that is part and parcel to the compilation of the Qur'an, its history, codification, reasons for revelation, its readings, and its transmission. The article contends that it is impossible to capture all these aspects without considering them in a logical, coherent, and interdependent way, considering especially that the issue of naskh (including its reality, meaning, and how to evaluate it) has been greatly debated. The article attempts to outline the methodological features needed to review many aspects of Islamic tradition, doing so through a scientific and accurate revision such that it would help preserve the integrity of this tradition against distortions, while authenticating it with the Qur'an and transcending what has no basis in the Qur’an.